Profiling of phospholipid classes and molecular species in human milk, bovine milk, and goat milk by UHPLC-Q-TOF-MS. (November 2022) - Sun, Yue; Tian, Songfan; Hussain, Muhammad; Lin, Shuang; Pan, Yue; Li, Xiaodong; Liu, Lu; Lu, Xinyu; Li, Chunmei; Leng, Youbin; Jiang, Shilong
Graphical abstract: Highlights: 73 and 156 differential lipid species are found in POS and NEG mode, respectively. Caprine MFGM contains high levels of SM, HexCer and Hex2 Cer than in others. Human MFGM phospholipid had low levels of SFA than in bovine and caprine MFGM. The differential biomarkers can be used to study the biological function of lipid. Abstract: This study aimed to identify differences of lipidome and fatty acid composition among human, bovine and caprine milk fat globule membrane (MFGM) using a lipidomics approach. In total, 11 lipid classes were determined, including PC, PE, SM, PG, PI, PS, Cer, PA, HexCer, Hex2 Cer and CL. Using positive and negative ionization modes, 73 and 156 common significantly differential lipid species were identified in three typical MFGM. The oleic acid (C18:1) was the dominant fatty acid in human (28.29 ± 0.04 g/100 g) and caprine (35.71 ± 0.02 g/100 g) MFGM, whereas Palmitic acid (C16:0, 29.13 ± 0.07 g/100 g) was the dominant fatty acid in bovine MFGM. In addition, there was no significant difference in long chain fatty acids between human MFGM and caprine milk. Overall, the results provide essential insights into differential lipids characterization in MFGM, along with a theoretical basis for the design of new infant formula.